Effect of vitamin-D supplementation on self-perceived health-related quality of life in postmenopausal women in Ludhiana, Punjab - Nimila Elsa Mathews; Paramita Sengupta; Anoop Ivan Benjamin (Wolters Kluwer Medknow Publications, 2021)
Postmenopausal women are routinely prescribed calcium and Vitamin-D supplements in view of their increased risk of osteoporosis and fractures. A community-based interventional study was undertaken to determine the effect of Vitamin-D supplementation on self-perceived health-related quality of life in 290 postmenopausal women over 6 months in 2015. Vitamin D (60,000 IU) was supplemented for 8 weeks. The CDC-Health-Related Quality-of-Life Questionnaire -14 was administered to the subjects at baseline and post intervention. The pre and postintervention responses were compared using Chi-square test and paired t-test as appropriate. There was a significant improvement in their overall general health status. Mean systolic blood pressure (BP) was reduced by 3.0% (P = 0.0705) and the mean diastolic BP by 3.2% (P = 0.0419). Post supplementation, high serum Vitamin-D levels was observed in 6.5% of the 92 subjects tested. Prescribing Vitamin D to postmenopausal women without checking the serum levels prior to supplementation may occasionally lead to toxicity.